2015
DOI: 10.1038/gt.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

Development of operational immunologic tolerance with neonatal gene transfer in nonhuman primates: preliminary studies

Abstract: Achieving persistent expression is a prerequisite for effective genetic therapies for inherited disorders. These proof-of-concept studies focused on AAV administration to newborn monkeys. Serotype rh10 AAV expressing ovalbumin and green fluorescent protein (GFP) was administered intravenously at birth and compared to vehicle controls. At 4 months postnatal age a second injection was administered intramuscularly, followed by vaccination at 1 year of age with ovalbumin and GFP. Ovalbumin was highest 2 weeks post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[30][31][32][33] Other studies that have focused on gene transfer in fetuses and newborns have shown longterm gene expression in muscles or the heart for several years without any evidence of adverse findings. [34][35][36][37][38] By contrast, when AAV vectors are administered to the liver of newborns, transgene expression can be significantly reduced over time, 39 making liver-directed gene therapy potentially challenging for the treatment of pediatric diseases. In this study, CNS and PNS vector ge- % neurons = mean percentage of hIDUA-positive neurons over total number of same-type neurons in frontal cortex pyramidal cells (15 fields); the hippocampus CA2-CA3 region (5 fields); the Purkinje cell layer of cerebellum (5 fields); the anterior horns of spinal cord sections (1 section per segment); and the DRG (up to 4 DRG per segment).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Other studies that have focused on gene transfer in fetuses and newborns have shown longterm gene expression in muscles or the heart for several years without any evidence of adverse findings. [34][35][36][37][38] By contrast, when AAV vectors are administered to the liver of newborns, transgene expression can be significantly reduced over time, 39 making liver-directed gene therapy potentially challenging for the treatment of pediatric diseases. In this study, CNS and PNS vector ge- % neurons = mean percentage of hIDUA-positive neurons over total number of same-type neurons in frontal cortex pyramidal cells (15 fields); the hippocampus CA2-CA3 region (5 fields); the Purkinje cell layer of cerebellum (5 fields); the anterior horns of spinal cord sections (1 section per segment); and the DRG (up to 4 DRG per segment).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of GCase in the skin of the knockout nGD mice precluded us from investigating this specifically. Nevertheless, immune tolerance towards a non-mammalian protein following fetal or neonatal gene delivery has been observed in non-human primate studies 25 and in mice this allowed effective re-administration of vector 26. Avoidance of an immune response following gene therapy is important.…”
Section: Main Textmentioning
confidence: 99%
“…In single-exposure studies with unmodified ADA LV, neither immune-deficient Ada −/− mice nor immune competent Ada +/− mice treated as neonates had no or little anti-vector IgG response. This finding is more likely related to the tolerizing effect of neonatal exposure to vector, as has been demonstrated in studies with adeno-associated viral vectors (AAV) 24, 25, 26. In Ada −/− mice treated at 4 months of age (after 4 months of ERT), the concentration of anti-vector antibody increased 15,000- to 20,000-fold, a magnitude of increase not observed in immune-competent Ada +/− mice treated as adults.…”
Section: Discussionmentioning
confidence: 82%